The effect of bitter melon (Momordica charantia L.) ethanol extract on tibia bone fracture healing in the Wistar strain rats (Rattus novergicus) based on radiological assessment, histopathology, and alkaline phosphatase levels - Rahman, Safrizal; Maryatun, Maryatun; Gan, Alex Kurniawan (Bali medical journal, 2020)
Introduction: Fracture is one of the most common health problem cases in the community. The goal of treatment for fractures is to restore the condition of the bone to pre-injury condition. This research aims to obtain a novel treatment for fracture healing. Bitter melon is a plant that is easily found and widely consumed in Indonesia. According to previous research, Bitter melon extract (Momordica charantia L.) can accelerate bone growth and repair after a fracture.Method: Â In this study, parameters used to assed fracture healing were histological, radiological, and alkaline phosphatase levels. This study used Bitter melon extract with 70% ethanol. Research groups consist of 3 groups with different doses and 1 control group where each group consisted of 6 subjects. The dosage used is 200 mg/Kg BW (P1), 300 mg/Kg BW (P2), and 400 mg/Kg BW (P3). Before being treated the subjects underwent factorization procedure and then treated used using bandages and wooden sticks for immobilization of fracture segments. Furthermore, the subjects were given Bitter melon extract twice a day for 84 days. Then checked according to the parameters seen. The data obtained are quantitative data which will be tested for normality and homogeneity first, then ANOVA test.Result: Callus formation findings shows the P1 groups showed the highest mean of callus formation among treatment groups after induced by Bitter melon ethanol extract of 200 mg/kg BW The results of LSD test in alkali phosphatase parameter between groups showed significant differences between the P1 group with controls (p = 0.000), P2 with controls (p = 0.000), P3 with controls (p = 0.000), P3 with P1 (p = 0.000) and P3 with P2 (p = 0.021)Conclusion: There was a significant effect of the administration of bitter melon fruit extract on the formation of callus formation in animal model after osteotomy.